Does the breakup process affect the reaction dynamics for the systems 17O, 17F + 58Ni at Coulomb barrier energies? - Parascandolo C.; Pakou A.; Nicoletto M.; Musumarra A.; Molini P.; Mazzocchi C.; Manea C.; Lotti P.; Lattuada M.; Inglima G.; La Commara M.; Guglielmetti A.; et al. (EPJ Web of Conferences, 2011)
The scattering processes of two mirror projectiles, the well bound 17O (Sn = 4.143 MeV) and the loosely bound radioactive 17F (Sp = 0.600 MeV), on the proton closed shell target 58Ni were measured at several energies around the Coulomb barrier. The experimental data were analyzed within the framework of the optical model to extract the reaction cross section and to investigate the role played by direct reaction channels at near-barrier energies. The comparison shows a similar behaviour for the two A = 17 projectiles despite their very different binding energies and suggests a rather small effect of the 17F breakup channel on the reaction dynamics.